RNAPhaSep: a resource of RNAs undergoing phase separation. Issue Volume 50:Issue D1(2022) (30th October 2021) - Zhu, Haibo; Fu, Hao; Cui, Tianyu; Ning, Lin; Shao, Huaguo; Guo, Yehan; Ke, Yanting; Zheng, Jiayi; Lin, Hongyan; Wu, Xin; Liu, Guanghao; He, Jun; et al.
Abstract: Liquid-liquid phase separation (LLPS) partitions cellular contents, underlies the formation of membraneless organelles and plays essential biological roles. To date, most of the research on LLPS has focused on proteins, especially RNA-binding proteins. However, accumulating evidence has demonstrated that RNAs can also function as 'scaffolds' and play essential roles in seeding or nucleating the formation of granules. To better utilize the knowledge dispersed in published literature, we here introduce RNAPhaSep (http://www.rnaphasep.cn ), a manually curated database of RNAs undergoing LLPS. It contains 1113 entries with experimentally validated RNA self-assembly or RNA and protein co-involved phase separation events. RNAPhaSep contains various types of information, including RNA information, protein information, phase separation experiment information and integrated annotation from multiple databases. RNAPhaSep provides a valuable resource for exploring the relationship between RNA properties and phase behaviour, and may further enhance our comprehensive understanding of LLPS in cellular functions and human diseases.